Identificación de las Condiciones de Seguridad, Salud y Medidas de Intervención Para los Recolectores de Café en el Municipio de Iquira del Departamento del Huila - Diaz Perdomo, Rafael Santiago; Tenjo Yaima, Diana Paola (Universidad Antonio Nariño, 2021)
Objective: This research project is carried out in the municipality of Iquira in the department of Huila with the objective of Identifying the health and safety conditions of coffee pickers, also identifying the sociodemographic profile, health and safety conditions; how to establish intervention measures according to the health and safety conditions diagnosed in the coffee pickers in the municipality of Iquira in the department of Huila. Methodology: the present study corresponds to a non-experimental cross-sectional descriptive investigation, with a mixed approach, the population for the research study is 3 coffee farms (20 coffee collectors) in the municipality of Iquira in the department of Huila. As instruments for collecting information, a survey was applied to identify health and safety conditions, the checklists were also applied in each of the farms, by means of which the risk matrices were collected. using the GTC45 methodology. Results: the sociodemographic and socioeconomic profile of the working population is identified, the risks to which coffee pickers are exposed are also identified, defining the priority risks. In the same way, the health and safety conditions to which they are exposed in their work area are identified, indicating that the workers have a good state of health since they do not present diseases caused by their work activity, on the other hand, it was found that the collectors have not suffered any type of work accident that has endangered their lives given the conditions in which they carry out their work. Conclusions: the workers who carry out the coffee harvest have a low profile, because the socioeconomic stratum ranges between 1 and 2, and the security conditions of the owners and their workers are currently not good because they have not adhered to the system of Social security, although they belong to Sisbén, cannot guarantee pensions or care from the occupational risk administrator When an accident occurs at work on the other hand It is evident that there are few controls that can ensure the good safety and health of the collectors in the work area due to the lack of extensive knowledge of the relevant control measures that can actually mitigate many identified hazards, as well as the details and importance of these when carrying out their activities.